Iranian Registry of Crohn’s and Colitis: study profile of first nation-wide inflammatory bowel disease registry in Middle East - Malekzadeh, Masoud M (Intest Res, 2019)
BACKGROUND/AIMS: A recent study revealed increasing incidence and prevalence of inflammatory bowel disease (IBD) in Iran. The Iranian Registry of Crohn’s and Colitis (IRCC) was designed recently to answer the needs. We reported the design, methods of data collection, and aims of IRCC in this paper. METHODS: IRCC is a multicenter prospective registry, which is established with collaboration of more than 100 gastroenterologists from different provinces of Iran. Minimum data set for IRCC was defined according to an international consensus on standard set of outcomes for IBD. A pilot feasibility study was performed on 553 IBD patients with a web-based questionnaire. The reliability of questionnaire evaluated by Cronbach’s α. RESULTS: All sections of questionnaire had Cronbach’s α of more than 0.6. In pilot study, 312 of participants (56.4%) were male and mean age was 38 years (standard deviation=12.8) and 378 patients (68.35%) had ulcerative colitis, 303 subjects (54,7%) had college education and 358 patients (64.74%) were of Fars ethnicity. We found that 68 (12.3%), 44 (7.9%), and 13 (2.3%) of participants were smokers, hookah and opium users, respectively. History of appendectomy was reported in 58 of patients (10.48%). The most common medication was 5-aminosalicylate (94.39%). CONCLUSIONS: To the best of our knowledge, IRCC is the first national IBD registry in the Middle East and could become a reliable infrastructure for national and international research on IBD. IRCC will improve the quality of care of IBD patients and provide national information for policy makers to better plan for controlling IBD in Iran.